Religion, Power, and Resistance New Ideas for a Divided World - Halafoff, Anna; Han, Sam; Starkey, Caroline; Spickard, James (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This volume explores the intersections of religion, power, and resistance in a fast-changing world. The authors herein seek to disrupt the sociology of religion's dominant paradigms, especially its overemphasis in Europe and the United States, as well as its preference for official religions as opposed to diverse worldviews in all of their manifestations from around the world: Africa, Asia, Australia, Europe, the Middle East, and North and South America. The papers in this volume explore ways of decentering the Global North and of decolonizing the sociology of religion's core concepts. They explore strategies used by newer and popular forms of religion to challenge existing power structures. Moreover, they examine the intersectionalities that privilege some people's religious lives and disprivilege others. They show how religion, spirituality, and non-religion are much more complex than the dominant paradigms have led us to believe. This volume seeks to generate robust discussion and critical reflection on new ideas for a divided world, thus contributing to the advancement of the discipline of religious sociology.